Autologous Conditioned Serum as a Novel Alternative Option in the Treatment of Unilateral Lumbar Radiculopathy: A Prospective Study - H. S., Ravi Kumar (Asian Spine J, 2015)
STUDY DESIGN: The study was conducted on patients who received autologous conditioned serum (ACS) as a line of treatment at the Orthopedics outpatient department of Post Graduate Institute of Medical Education and Research (PGIMER, Chandigarh) from January 2011 to June 2012. Of the 1,224 patients, 20 males or females were included in the study based on the inclusion and exclusion criteria. The institutional board of PGIMER approved the study before it was initiated. PURPOSE: To study the efficacy of ACS in the treatment of unilateral lumbar radiculopathy. OVERVIEW OF LITERATURE: Interleukin (IL)-1 appears to be of special importance among the cytokines identified in orthopedic diseases. ACS contains high concentrations of IL-1 receptor antagonist, antagonist to IL-1 in that is a biochemical 'sensitizer' of nerve roots in radiculopathy. METHODS: We included 20 patients with unilateral lumbar radiculopathy after obtaining informed consent. We prepared ACS as described by Meijer et al. Under bi-planar fluoroscopic imaging in anterior-posterior and lateral views, ACS was administered via epidural perineural technique. Patients in both groups were evaluated by quadruple visual analogue scale, straight leg raising test, revised Oswestry disability index, and 12-Item Short Form of Health Survey before and after epidural injections at 3 weeks, 3 months, and 6 months. RESULTS: There was a statistically significant change in all parameters from pre-injection to first, second, and third follow-up (p<0.001). CONCLUSIONS: ACS can modify the disease course in addition to reducing pain, disability and improving general health.